Archaeology and the Biblical record - Alpert, Bernard; Alpert, Fran. (Lanham, Md. : Hamilton Books, 2012)
In the 6th century BCE, Jerusalem and Judea were destroyed by the Babylonians. This traumatic event created the need to construct and articulate a comprehensive past that would give meaningful context to the identity of the Israelites. New modes of communal organization and worship during this period formed the foundation of Second Temple Jerusalem and early Christianity. Readers will be able to revisit familiar Bible stories and reach a better understanding of these events through the lens of modern archaeology. Archaeology and the Biblical record challenges traditional views of the scripture while respecting the religious sensitivities of the reader. This bold text invites both Jewish and Christian biblical scholars to rethink basic assumptions and reformulate their instructional methods. Accessible and concise, this fresh look at Bible history is written for teachers, members of the clergy, and general readers, providing answers to the many historical dilemmas confronted in the course of studying the Bible.
Includes bibliographical references.
Keywords: Bible -- Antiquities; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books